Comparing Utility Functions in Efficiency Terms: Reply - Weisbrod, Burton A. (American Economic Review, 2016)
If utility functions can be compared in efficiency terms, as I argued is sometimes the case (see my earlier paper), it follows that there is a new research area for economists to explore. To be sure, no analytic perspective, no matter how useful it may be, is without problems. For example, as Dana Stevens and James Foster have correctly pointed out, the possibility (though not the certainty) of cyclic ranking of utility functions exists if more than two types are compared. Their comment is, I believe, intended not as criticism of the utility function comparability perspective but as a call for more research; for example, on the efficiency properties of various types of utility functions, and on the responsiveness of attainable commodity sets to changes in preferences. The point is that there do exist researchable questions that are suggested as soon as we recognize the possibility of subjecting utility functions to analysis within a Paretian framework. Conventionally such questions have not been asked, partly because they were regarded as equity matters on which economists had little to say normatively, and partly because the factors shaping utility functions have been regarded as lying outside the domain of economics. It certainly is premature to say that we now know enough to conclude that on efficiency grounds alone, resources shouldor should not -be devoted to shaping utility functions. Yet to entertain even the possibility that one type of utility function can be preferred to another, and that changing such a function may be efficient, is to reach out in a bold new direction. Important conceptual issues as well as vital public policy questions are at stake.